Impact of homestead housing on the allocation of financial assets of Chinese rural households. Issue 1 (2nd January 2023) - Hu, Junhui; Han, Hongfang; Zhang, Zhaonan; Wu, Xin
Abstract: Using CHFS data and quantile regression method, this study empirically analyzes the impact of current homestead housing on rural household financial asset allocation in China. The main findings are as followings: The homestead housing system effectively protects the residential rights and interests of rural residents, but it is constrained by the system and fails to give full play to the investment value; Only on the premise of meeting the needs of family mobility, homestead housing can effectively play the wealth effect; In the family risk portfolio, homestead housing and risk financial asset allocation are mutually exclusive; In private lending, the impact of homestead housing on the provision of loans is more complex, but not always statistically significant; The impact of homestead housing on family financial asset allocation shows obvious heterogeneity and differentiation. Further releasing the liquidity of homestead housing, enriching the level of rural financial products and services, and encouraging rural families to appropriately participate in venture financial asset investment are the reform direction to improve the welfare level of rural families and optimize the allocation of family assets.